DEVELOPMENT AND PSYCHOMETRIC PROPERTIES OF OPPOSITIONAL DEFIANT BEHAVIORS SCALE FOR ADOLESCENTS - Abid, Mueen; Bano, Zaqia (Pakistan Armed Forces Medical Journal, 2020)
Objective: To construct a scale and psychometric properties for the assessment of oppositional defiant behaviors of adolescents in Urdu language. Study Design: Cross sectional analytical study. Place and Duration of Study: Department of Psychology, University of Gujrat, from May 2018 to Dec 2018. Methodology: The initial item pool of 48 items was generated with the help of DSM 5 description of oppositional defiant behaviors, literature review and three focus groups with target population. Among the 47 expert evaluated items after pilot studys 45 items were retained which included the three dimensions of oppositional defiant behaviors including irritable mood, argumentative behaviors and vindictiveness. Furthermore, in the final administration of this scales data were collected from 500 adolescents from the educational institutions and community of Gujrat using self-reported questionnaire. The exploratory factor analysis (EFA), confirmatory factor analysis (CFA) and reliability analysis were implied for data scrutiny. Results: The final administration of 45 items was handed over to 500 participants. The model fit showed a p-value of .000 that established the structure validity and significance of the items to its subscales. At the final stage among the 45 items 12 were reliable for further use. Conclusion: A scale to gauge oppositional defiant behaviors of adolescents in Urdu language is competently established with 12 questions and three sub-scales.